High trait emotional intelligence in men: Beneficial for perceived stress levels but disadvantageous for the physiological response to acute stressors?. Issue 3 (24th January 2018) - Thomas, Laura Isabell; Fuchs, Reinhard; Klaperski, Sandra
Abstract : This study examined the relationship between trait emotional intelligence (EI) and stress in 110 male employees. Particularly, the association between trait EI and perceived chronic stress, occupational stress, and the physiological stress response was examined. Trait EI, perceived chronic stress, and occupational stress levels were assessed via questionnaires. The physiological stress response was measured by means of salivary free cortisol and heart rate variability (HRV) in response to the Trier Social Stress Test for Groups. Consistent with previous findings, men with high trait EI showed significantly lower perceived chronic and occupational stress levels than men with low trait EI. However, men with high trait EI also showed significantly higher cortisol reactivity than their low trait EI counterparts. Similarly, HRV in men with high trait EI appeared to be lower than in men with low trait EI but HRV differences between groups were not significant. Our findings suggest that trait EI might play a critical role in the stress regulation process but due to the cross‐sectional design of the study no causal conclusions can be drawn. Experimental studies need to explore further whether and how trait EI affects psychological and physiological stress responses.